2016
DOI: 10.1116/1.4965304
|View full text |Cite
|
Sign up to set email alerts
|

Gas uptake of 3D printed acrylonitrile butadiene styrene using a vacuum apparatus designed for absorption and desorption studies

Abstract: We describe a vacuum apparatus for determining the outgassing rate into vacuum, the diffusion coefficient, and the amount of gas absorbed for various materials. The diffusion coefficient is determined from a model applied to time-dependent desorption data taken using a throughput method. We used this method to determine the diffusion coefficient, D, for H2O in 3-D printed acrylonitrile butadiene styrene (ABS). We found DH2O = 8.3 × 10−8 cm2/s ± 1.3 × 10−8 cm2/s (k = 1; 67% confidence interval) at 23.2 °C. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…3-D printed ABS has a higher WVR value (0.25%) compared to PC (0.14%) [40]. In fact, it has been reported that at least 80% out of all gas absorbed in ABS is water vapour [41] and that most water vapour selectively outgasses in the mTorr pressure range [42][43]. In this study, all outgassing data was collected below 1 mTorr, indicating that ABS had dehydrated more effectively.…”
Section: Discussionmentioning
confidence: 62%
“…3-D printed ABS has a higher WVR value (0.25%) compared to PC (0.14%) [40]. In fact, it has been reported that at least 80% out of all gas absorbed in ABS is water vapour [41] and that most water vapour selectively outgasses in the mTorr pressure range [42][43]. In this study, all outgassing data was collected below 1 mTorr, indicating that ABS had dehydrated more effectively.…”
Section: Discussionmentioning
confidence: 62%
“…In support of this assertion, we have previously determined that water was adsorbed by 3D printed ABS at a capacity of 0.35% w/w. 29 Similarly, Cohen and coworkers have shown that MOFs within a polymer matrix are less susceptible to humid conditions. 17,20 While we are working with a degraded form of MOF-5 in our composites, further measurements of H 2 uptake by our 3D printed objects remain valuable.…”
Section: Resultsmentioning
confidence: 93%
“…This technique has been used previously by the authors and is described in detail in other publications. 1,16 Briefly, the gate valve was placed between an all-metal valve and a spinning rotor gauge as shown in Figure 6(b). The GV remained in an open position and never closed during the outgassing measurement.…”
Section: Description Of the Gate Valve And Vacuum Bakementioning
confidence: 99%